Levy, Charmain & Alberio, Marco, eds., Reimagining the Urban Commons in Italy. Reform, Social Innovation and Transformation, Bingley, UK: Emerald Publishing Limited, 2026 - D'Ambrosi, Lucia (PARTECIPAZIONE E CONFLITTO, 2026)
For Book Reviews Abstract is not required